Experimental Histopathological Comparison of Fresh Frozen Allograft and Autograft Cartilage - Sutcu A. O.; ÇALIM Ö. F.; Polat E.; AYDIN M. Ş.; KULAKSIZ Y.; AKSOY M. F.; ÖZTURAN O. (My University, 2025)
BackgroundCartilage grafts are essential in rhinoplasty, particularly in revision cases that require structural support. Fresh frozen cartilage allografts (FFCA) have been proposed as an alternative to autografts to avoid donor site morbidity; however, their biological properties remain insufficiently studied. This study aimed to evaluate the histopathological and immunohistochemical characteristics of FFCA compared with autograft cartilage in a rabbit model, focusing on antigenicity, cellular viability, inflammation, and fibrovascular integration. MethodsEight adult New Zealand white rabbits underwent bilateral auricular cartilage harvesting. The right ear cartilage from each rabbit was immediately implanted subcutaneously into its own paraspinal region as an autograft. The left ear cartilage was cryopreserved at -80 degrees C for two weeks and subsequently implanted as an FFCA into the paraspinal region of the next consecutively numbered rabbit. All grafts were harvested and analyzed histologically after three months. ResultsBoth groups exhibited preserved cartilage architecture and fibrovascular integration. No significant differences were observed in graft resorption, fibrosis, or calcification (p > 0.05). However, FFCA showed a significant reduction in viable chondrocytes (p < 0.05) and lower glial fibrillary acidic protein expression, suggesting diminished cellular activity. Despite maintaining structural stability, FFCA demonstrated reduced biological viability compared with autografts. ConclusionsFFCA preserves structural integrity and integrates with surrounding tissue but exhibits lower cellular viability than autografts. While it may represent a useful alternative in rhinoplasty, further studies are required to optimize preservation techniques and assess long-term outcomes. No Level AssignedThis journal requires that authors assign a level of evidence to each submission to which Evidence-Based Medicine rankings are applicable. This excludes Review Articles, Book Reviews, and manuscripts that concern Basic Science, Animal Studies, Cadaver Studies, and Experimental Studies. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; Cerrahi; Klinik Tıp; Klinik Tıp (Med); Surgery; Clinical Medicine; Clinical Medicine (Med)